2014
DOI: 10.1186/1939-4551-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunological cross-reactivity between olive and grass pollen: implication of major and minor allergens

Abstract: BackgroundGrasses and olive trees are the most common sources of allergenic pollen worldwide. Although they share some allergens, there are few studies analyzing the in vitro cross-reactivity between them. The aim was to define the cross-reactivity between Olea europaea and Phleum pratense using well-characterized sera of allergic children from Madrid, Spain.Methods66 patients (mean age 10.32+/−4.07 years) were included in the study. All suffered from rhinoconjuntivitis and/or asthma and had a positive skin te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Approximately 65---85% of grass-sensitized patients are positive for these allergens, which is why they are deemed major allergens. 5,15 In this study, it was not detected in isolation but 44.4% of the patients presented positive values. Seven children and 13 adults with positive sensitization results were detected for this allergen, with the percentage of sensitized patients being higher in adults.…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Approximately 65---85% of grass-sensitized patients are positive for these allergens, which is why they are deemed major allergens. 5,15 In this study, it was not detected in isolation but 44.4% of the patients presented positive values. Seven children and 13 adults with positive sensitization results were detected for this allergen, with the percentage of sensitized patients being higher in adults.…”
Section: Discussioncontrasting
confidence: 44%
“…17 Phl p6 is an allergen associated with proteins that bind calcium ions. 15 It is sequentially very similar to Phl 5 and therefore the two exhibit cross-reactivity. There are few cases of exclusive positivity to this marker.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Up to now, minor allergens are usually not controlled during the production of allergen products. Although some observations imply a link between more severe allergy symptoms and sensitization to minor allergens, their relevance for safety and efficacy of allergen products is virtually unknown and data from controlled clinical trials are lacking. While standardization of allergen product manufacturing and composition has generally advanced in the past decade, neither raw materials nor production processes or storage conditions are standardized with regard to minor allergens .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, sensitization to profilin was identified as a marker for more severe symptoms in grass pollen allergic patients . In addition, it has been reported that high IgE levels to minor allergens are often associated with extensive cross‐reactivities . Nevertheless, there exists only one published example of a minor allergen specification: After discovering that an elevated level of the glucanase Ole e 9 in some product batches was associated with an increased rate of adverse events during AIT, the respective manufacturer introduced a specification limiting the content of this minor allergen .…”
Section: Introductionmentioning
confidence: 99%